Drivers for young adults’ continued knowledge sharing in Chinese virtual academic communities - Feng, Shan (My University, 2018)
This research for this thesis aimed to determine the drivers for young adults’ continued knowledge sharing in virtual academic communities (VACs), and to help VACs managers identify significant factors that affect young adults. Smart Partial Least Squares (PLS) path modelling was used to analyse the research data. On the basis of the data analysis, hypotheses were judged, and results were analysed. Finally, this thesis offered a conclusion of drivers for young adults’ continued knowledge sharing in Chinese VACs. This is a quantitative research project based on a survey. After reviewing the prior research about continued knowledge sharing and VACs. This study primarily discusses the definition of VACs. Next, the similarities and differences between the representative Chinese and global VACs are illustrated. Based on theories and research status, the research model is built in the third chapter. The main body of the model was built based on the expectation-confirmation model of IS continuance (ECM-IS). The IS success model is the basis upon which to add external variables: reputation (RE), social relationships trust (SRT), academic information quality (QL), academic information quantity (QT) and user interface (UI). In this research model, electronic survey questionnaires were distributed, and data were collected from young adults who have used Chinese VACs. By using the SmartPLS3.0 software program, PLS and bootstrapping algorithms were used to test the construct’s reliability, validity and significance. At the end of this study, it verifies whether the hypotheses are correct, and concludes the thesis in accordance with the aforementioned explanations and data analyses. Also, discussions and limitations are presented. Through this research, it was found that RE, QL, QT and UI are four drivers for young adults’ CoB. Moreover, RE and SRT are two factors that influence young adults’ perceived usefulness (PU). And then, CoB and PU are both influence factors of satisfaction (SA). Next, SA and PU may influence the continued knowledge sharing (CKS) in directly. Of the above influence factors, satisfaction is the most important one affecting young adults’ continued knowledge sharing.
Keywords: Continued knowledge sharing, virtual academic communities, influence factors, young adults, structural equation modelling